A companion to the eighteenth-century English novel and culture - Backscheider, Paula R., 1943-; Ingrassia, Catherine (Blackwell companions to literature and culture, 2005)
Aims to furnish readers with a cultural studies methodology and a vision of the eighteenth-century novel in its political, aesthetic, and moral contexts. This volume is divided into three parts exploring formative influences on the eighteenth-century novel, its engagement with the issues and philosophies of the period, and its lasting legacy.